Radical Combustion: New Concept For Two Stroke Engines - Saqaff A Al-Kaf; Ahmad Suhaimi; Hakim A Abbas (ASEAN Journal on Science and Technology for Development, 2000)
Radical Combustion: New Concept For Two Stroke Engines